Optical neuromielitiis of devic. A case report - Gamez Morales , Lorenzo Antonio; Andino Rodriguez, Francisco; Espinoza Barcia , Alicia; Vidal Coronel , Maria Fernanda (Revista Universidad de Guayaquil, 2012)
A woman of 31 years old with diagnosis of Optical neuromielitis (NMO) presents clinical features of left optical atrophy, right optical neuritis and cervical transverse mielitis with progressive evolution that has produced him visual disability and important motor affection. We made some reflections about Multiple Sclerosis and Optical Neuromielitis and the possible therapeutics to a good life quality and reduce the incapacity of these patients. Is necessary to made an Epidemiological study in Ecuador for determinate the prevalence of this pathologies.